The Impact of EWOM, Brand Image, and Content Marketing on Purchase Decision with Country of Origin as a Moderating Variable - Rosyifa Salsabila Auliya Sahili; Ma’mun Sarma; Mimin Aminah (Eduvest - Journal of Universal Studies, 2026)
The increasing need for clean water in industrial areas demands a reliable and sustainable water supply system. This study aims to determine the optimal strategy for meeting clean water supply through optimizing the operational and maintenance costs of the water utility network at WTPs in industrial areas. The strategies analyzed include O&M strategies, small CAPEX strategies through the implementation of Streaming Current Monitors (SCMs) and supporting instrumentation, and large CAPEX strategies in the form of WTP construction or expansion. The research method uses Present Value (PV) and Life Cycle Cost (LCC) based financial analysis with a 20-year analysis period and a discount rate of 8%, based on historical WTP operational data and investment estimates. Scenario and sensitivity analysis were conducted to strengthen decision making. The results showed that the O&M strategy is the most optimal strategy and is the main priority because it provides the highest cumulative cost savings without initial investment, with PV Saving OPEX and MEX of IDR 230.07–677.51 million, and IDR 495.26 million in the moderate scenario. Small CAPEX strategy produces a positive NPV Saving of IDR 51.48 million but is sensitive to initial investment and the level of chemical savings. Meanwhile, the large CAPEX strategy has a Total Life Cycle Cost of IDR 57,415.00 million and is more appropriate as a medium to long-term solution to increase capacity and supply reliability. This study recommends implementing the strategy in stages to maintain the sustainability of clean water services and the efficiency of industrial area operational costs.